2011
DOI: 10.1016/j.breast.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

SISMAMA—Implementation of an information system for breast cancer early detection programs in Brazil

Abstract: As national health systems seek to apply breast cancer screening recommendations to an entire population of women (within target age ranges for which there is evidence that screening reduces mortality), the volume of screening tests and resulting diagnostic investigations arising from abnormal test results-and the cost associated with them-will grow dramatically. Population-based early detection (screening) programs will need information systems and management tools to help these programs. This report describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 2 publications
1
20
0
9
Order By: Relevance
“…No SISMAMA, subsistema do SIA instalado nos serviços públicos ou nos prestadores contratados pelo SUS e nas Coordenações de Saúde da Mulher das secretarias estaduais e municipais de saúde, são registrados os dados de solicitação e resultados de exames de mamografia, citopatoló-gicos e anatomopatológicos de mama (biópsia e peça cirúrgica) 12 .…”
Section: Métodosunclassified
See 1 more Smart Citation
“…No SISMAMA, subsistema do SIA instalado nos serviços públicos ou nos prestadores contratados pelo SUS e nas Coordenações de Saúde da Mulher das secretarias estaduais e municipais de saúde, são registrados os dados de solicitação e resultados de exames de mamografia, citopatoló-gicos e anatomopatológicos de mama (biópsia e peça cirúrgica) 12 .…”
Section: Métodosunclassified
“…Em 2009, foi implantado o Sistema de Informação para o Controle do Câncer de Mama (SISMAMA) 11 , para padronização da coleta de dados sobre o rastreamento, o diagnóstico e o tratamento do câncer da mama em todo o país e permitir a avaliação das ações de controle da doença 12,13 .…”
Section: Introductionunclassified
“…The mean time between presentation of symptoms and diagnosis is 72-185 days, which leads to high rates of advanced stage diagnosis, with 37.0% in stage III and IV, different from that observed in the private sector, where this rate is 16.2%. 8 Regarding health management 11,12 and information systems for the support of health management, 13,14 four articles were selected. Assessing the origin-destination flow of outpatient visits and hospitalizations related to breast cancer, we observed that the treatment is generally performed in large cities and in reference centers, and patients travel distances greater than 150 km from their city source.…”
Section: Methodsmentioning
confidence: 99%
“…12 The SISMAMA system showed promising results with 50% of the examinations performed in the age group 50-69 years and about 66% of mammography reports were performed in a period inferior to 30 days. 13 National coverage is low, including 32% of women in the 50-59 age group and 25% in the 60-69 age group, though this actually depends on the age group of the macro-region. In general, the coverage of women in the 50-59 age group is higher in the Southern and Southeastern states, and lower in the North and Northeast.…”
mentioning
confidence: 99%
See 1 more Smart Citation